2014
DOI: 10.1111/cei.12354
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+CD39+ regulatory T cells produce adenosine upon co-expression of surface CD73 or contact with CD73+ exosomes or CD73+ cells

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
217
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(238 citation statements)
references
References 40 publications
13
217
0
2
Order By: Relevance
“…Adenosine is a wellknown immunosuppressive factor that signals to effector T cells (Teffs) via the adenosine A 2A receptor (A2AR) to upregulate cAMP levels and inhibit Teff function (53). TEX carry CD39 and CD73, the ectonucleotidases responsible for ATP-dependent adenosine production, thereby serving as vehicles for the delivery of these enzymes to target cells (54). CD39 + Tregs in the TME are beneficiaries of this process, as continuous TEX-mediated CD73 delivery enables them to increase adenosine production and upregulate immunosuppressive functions (55).…”
Section: Functional Attributes Of Texmentioning
confidence: 99%
“…Adenosine is a wellknown immunosuppressive factor that signals to effector T cells (Teffs) via the adenosine A 2A receptor (A2AR) to upregulate cAMP levels and inhibit Teff function (53). TEX carry CD39 and CD73, the ectonucleotidases responsible for ATP-dependent adenosine production, thereby serving as vehicles for the delivery of these enzymes to target cells (54). CD39 + Tregs in the TME are beneficiaries of this process, as continuous TEX-mediated CD73 delivery enables them to increase adenosine production and upregulate immunosuppressive functions (55).…”
Section: Functional Attributes Of Texmentioning
confidence: 99%
“…Cytometry revealed an increased number of CD8 + (T suppressor/cytotoxic) and CD19 + splenocytes seemed to play an important role. We intend, in the near future, to carry out a more detailed study of splenocytes, among others, to investigate the presence of markers characteristic for regulatory T and B cells (Saze et al 2013, Schuler et al 2014, Figueiro et al 2016. Hypertrophic changes in renal glomeruli might be connected with increased concentration of bFGF and VEGF in the sera of E group progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, CD39+/CD73+ microvesicles were discovered in different cancer cell types and were actually shown to be able to suppress T-cell function through adenosine production [106]. Contributing to this body of evidence, it was demonstrated that CD4+CD39+Tregs act in cooperation with CD73-expressing-exossomes or with other lymphocytes expressing CD73 to mediate ADO-driven immune suppression [107]. Taken together, these studies clearly build a complex scenario in which adenosine production is the final product of a range of possible dynamic processes that include Tregs, as well as cooperative arrangements between different cell types and membrane-bound vesicles.…”
Section: Regulatory T-cells and Adenosinementioning
confidence: 99%